Policy Conflict Between President Joko Widodo And Governor Of DKI Jakarta Anies Baswedan In Fighting The Spread Of Covid -19 - Agus Sugiharto; Auderey G. Tangkudung (Jurnal Syntax Transformation, 2020)
The spread of COVID-19 in Jakarta and Indonesia is very fast, especially in Jakarta and its surroundings. The central government led by President Jokowi has policies to combat the spread of COVID-19, while Jakarta Governor Anies Baswedan also has separate policies to combat the spread of COVID-19. There are two different policies, and both have their own view in combating COVID-19. This paper discusses these policies differences, the motives behind these differences, and how this policy conflict end. Further, this paper also analyzes whether or not this policy conflict represents both sides political view, and whether or not this policy conflict is related to the 2024 Presidential Election, and also which policy will be the best option for the people of Indonesia. The research methodology used is a qualitative methodology based on researching social media coverage and analyzing the news and writings contained in these media.